2012
DOI: 10.2147/opth.s27423
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vitreous and serum vascular endothelial growth factor levels, control of diabetes and microalbuminuria in proliferative diabetic retinopathy

Abstract: BackgroundDiabetic retinopathy is a serious microvascular disorder of the retina. Vascular endothelial growth factor (VEGF) expression, induced by high glucose levels and hypoxia, is a main feature in retinopathy. The aim of this study was to evaluate the relationship between vitreous and serum VEGF levels and control of diabetes and microalbuminuria in patients with proliferative diabetic retinopathy.MethodsSixty-five patients were enrolled in this case-control study, comprising 30 patients with proliferative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
3
14
1
Order By: Relevance
“…As we discussed before, the relationship between VEGF concentration in vitreous fluid and in plasma were also in controversy. A significant correlation between vitreous and plasma VEGF levels in patients with DR was reported by Baharivand N [30] and YR Jiang [25] . Both of their studies showed VEGF in vitreous were slightly higher than in plasma, which are in consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 67%
“…As we discussed before, the relationship between VEGF concentration in vitreous fluid and in plasma were also in controversy. A significant correlation between vitreous and plasma VEGF levels in patients with DR was reported by Baharivand N [30] and YR Jiang [25] . Both of their studies showed VEGF in vitreous were slightly higher than in plasma, which are in consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 67%
“…A variety of reports demonstrated that VEGF content was elevated in serum or vitreous cavity prior to the appearance of discernible vascular lesions, and there were positive correlations between VEGF and blood glucose levels 25 26 27 . The source of elevated VEGF content in DR is still not fully elucidated, but may include the autocrine mechanism in retinal endothelial cells 23 24 28 , and the paracrine mechanisms in retinal pigment epithelial (RPE) cells or macroglia cells 29 30 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was revealed a significant correlation between serum and vitreous level of VEGF in proliferative diabetic retinopathy patients. 38 In turn, Romano et al 39 revealed altered expression of three microRNA both in rat retinas and in serum of AMD patients. However, only a few reports showed changed expression of various mRNAs or proteins in PBMCs obtained from AMD patients.…”
Section: Discussionmentioning
confidence: 99%